Asian Americans and workplace discrimination: The interplay between sex of evaluators and the perception of social skills1. (24th April 2012) - Lai, Lei; Babcock, Linda C.
Summary In two role‐playing scenarios, we investigate how White male and female evaluators perceive an Asian American versus White job candidate on the dimensions of competence and social skills and how these perceptions affect evaluators' decisions in hiring and promotion. Specifically, Study 1 examines how the perceptions of competence and social skills affect Asian (versus White) college graduates' chance of obtaining a non‐technical (versus technical) position, and Study 2 tests how these perceptions affect Asians' probability of promotion relative to Whites'. Our findings suggest that female evaluators were less likely to select Asian than White candidates into positions involving social skills and were less likely to promote Asian than White candidates into these types of positions. Furthermore, female evaluators' perception that Asians were less socially skilled than Whites mediated both of these decisions. This paper contributes to the understanding of workplace discrimination of Asian Americans. Copyright © 2012 John Wiley & Sons, Ltd.